(untitled) (Biological Sciences - PJSIR, 2004)
In an attempt to enhance the nutritional quality of cassava products (flour & gari), Baker’s yeast was used in the fermentation (solid media) of cassava pulp. The mash obtained was subsequently processed into flour and gari (the forms in which cassava products are popularly consumed in Nigeria) and analyzed. The protein (flour, 10.90%; gari, 6.30%) and fat (flour, 4.50%; gari, 3.00%) contents of the products were high. Conversely, the tannin (flour, 0.2%; gari, 0.1%) and cyanide (flour, 9.5mg / kg; gari, 9.1mg / kg) contents were low, though, the cassava flour had higher protein, fat, tannin and cyanide contents than gari. The results indicated that Baker’s yeast, a cheap and non-pathogenic saprophyte, could be used in enhancing the nutritional potentials of cassava products by increasing nutrients (protein and fat) and decreasing antinutrient contents (tannin and cyanide). However, nutrient increase was higher in cassava flour while the antinutrient decrease was higher in gari.